Degradation of Triadimefon Compounds in Bayleton 250 EC Pesticides by Sonolysis, Ozonolysis and Sonozolysis - Kamila, Rahmi (International Journal of Natural Science Studies and Development (IJOSS), 2024)
The increase in the agricultural sector is supported by the use of pesticides to kill pests and diseases in plants. However, the continuous use of pesticides in excessive amounts can have a detrimental impact on the environment, especially the waters around agricultural land. Therefore, efforts are needed to degrade pesticide residues containing triadimefon compounds that pollute the environment such as sonolysis, ozonolysis, and sonozoisis methods. These three methods are organic compound degradation methods that utilize OH radicals to degrade organic compounds. Based on the data obtained, the sonolysis method with the addition of TiO2-anatase catalyst produced a degradation percentage of 76.25% after degradation for 150 minutes. While in a much shorter time, namely 15 minutes, using the ozonolysis method without the use of a catalyst, triadimefon can be degraded by 69.10%, and 71.87% with the sonolysis method. Since only a small amount of triadimefon is degraded by the sonozolysis method, it is more effective to use the ozonolysis method to degrade this triadimefon compound.